VITAL SIGNS MEASUREMENT IN AESTHETIC PRACTICE: AN ESSENTIAL SAFETY STANDARD (CIPEEX, 2025)
The assessment of vital signs, traditionally associated with clinical settings, is equally crucial in aesthetic practice. The objective of this study was to reinforce the importance of vital signs measurement as a pillar of biosafety and professional ethics, considering the increasing use of technologies that can induce physiological responses in patients. To achieve this, a narrative review of the scientific literature was conducted using the PubMed, SciELO, and LILACS databases, focusing on the basic parameters of blood pressure, heart rate, respiratory rate, body temperature, and oxygen saturation. The research, carried out between 2023 and 2025, analyzed articles that address the importance of these indicators for decision-making in health and aesthetic contexts. The results indicate that the correct and systematic measurement of vital signs allows for the identification of contraindications and reduces the risk of complications. For example, detecting uncontrolled hypertension may lead the professional to postpone or modify a procedure. This practice also strengthens patient trust and elevates the standard of care. The monitoring of vital signs, which can be done with the help of technology, is a valuable screening tool that supports safe therapeutic decision-making. In conclusion, the inclusion of vital signs monitoring in the pre-procedure physical examination is indispensable to ensure safety and individualized care, supporting evidence-based interventions. This practice should not be optional, but a standard of conduct for all professionals in the aesthetic field.